UNDERSTANDING CAREER DEVELOPMENT NEEDS AND CAREER COUNSELING STRATEGIES FOR REFUGEES - Sobko, Yuliia (Collection of scientific papers «ΛΌГOΣ», 2022)
According to the UN Refugee Agency, by the end of 2021, 89.3 million people were forcibly displaced worldwide due to persecution, conflict, violence, or human rights violations. As of May 2022, 100 million individuals were forcibly displaced worldwide. This accounts for an increase of 10.7 million people displaced from the end of the previous year, propelled by the war in Ukraine and other deadly conflicts.